2015
DOI: 10.1016/j.imbio.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid and CD38 ligation differentially regulate CD1d expression and α-galactosylceramide-induced immune responses

Abstract: The MHC class-I like molecule CD1d presents glycolipid antigens and thereby activates invariant natural killer-T (NKT) cells. However, little is understood regarding the regulation of its expression. All-trans-retinoic acid (RA) and CD38, which is itself a target of RA, both independently regulate the differentiation of antigen presenting cells. In the current study, we treated human THP-1 cells and murine splenic cells with RA, with and without antibody-mediated ligation of cell-surface CD38. Whereas a physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Thus far, the role of vitamin A status on iNKT cells has been unclear. In one article, increased expression of CD1d on a myeloid cell line by RA was observed in vitro (40). It has been also reported that parenteral injection of RA decreased cytokine production by iNKT cells and related liver damage (41).…”
Section: Discussionmentioning
confidence: 98%
“…Thus far, the role of vitamin A status on iNKT cells has been unclear. In one article, increased expression of CD1d on a myeloid cell line by RA was observed in vitro (40). It has been also reported that parenteral injection of RA decreased cytokine production by iNKT cells and related liver damage (41).…”
Section: Discussionmentioning
confidence: 98%